Proteção do trabalhador da saúde na covid-19: uma análise documental - Siqueira, Izabella Sant'Anna (2023)
Introduction: The pandemic caused by the coronavirus (SARS-CoV-2) has created a global public health emergency. The central element was the role of healthcare workers in confronting the pandemic and combating COVID-19, and the protection of professionals who worked on the front line should be included in this context, aiming to preserve their physical and mental health. Objective: The general objective of this research is to analyze the regulations and protocols published to combat the COVID-19 pandemic by the Government of the State of Mato Grosso/Secretariat of State for Health, comparing them with the recommendations and technical guidelines of PAHO/WHO /BRAZIL about the health of healthcare workers. Methodology: This is qualitative research with documentary analysis of the regulations and protocols adopted for the health of healthcare workers in the context of the COVID-19 pandemic, in the years 2020 to 2021. 11 PAHO/WHO Technical Guidelines were selected for analysis /BRAZIL and 23 Regulations published by the State Executive, relating to the topic of worker health, which were divided into thematic categories. Results: In the thematic category of worker protection, publications on the rational use of personal protective equipment, occupational safety and health were highlighted; in the work environment thematic category, the publication of protective measures such as shifts and teleworking is identified, thus ensuring distancing in the work environment, in addition to the removal of workers in the risk group for COVID-19; in the mental health category, the issuance of regulations regarding mental health monitoring and psychosocial support for workers. Final considerations: This research demonstrated that the State Department of Health of Mato Grosso, following the technical guidelines issued by PAHO/WHO/BRAZIL, published regulations for worker protection.